TRANSFER OF LEARNING TO ACQUISITION: COMMUNICATIVE APPROACH CONTRIBUTION - Hanafi Hanafi (University of Muhammadiyah Purwokerto, 2009)
This essay discusses a controversy the author notices in the Language Acquisition theories. The author sees that a controversy over the transfer of learnt knowledge to acquisition exists between two outstanding experts in the field. The author proposes some arguments and conditions for the transfer to take place. For the clarity of the discussion, several relevant theories are reviewed as the background from which the problem arises.